Plasmodium falciparum FIKK Kinase Members Target Distinct Components of the Erythrocyte Membrane - Nunes, Marta C. (Public Library of Science, 2010)
BACKGROUND: Modulation of infected host cells by intracellular pathogens is a prerequisite for successful establishment of infection. In the human malaria parasite Plasmodium falciparum, potential candidates for erythrocyte remodelling include the apicomplexan-specific FIKK kinase family (20 members), several of which have been demonstrated to be transported into the erythrocyte cytoplasm via Maurer's clefts. METHODOLOGY: In the current work, we have knocked out two members of this gene family (Pf fikk7.1 and Pf fikk12), whose products are localized at the inner face of the erythrocyte membrane. Both mutant parasite lines were viable and erythrocytes infected with these parasites showed no detectable alteration in their ability to adhere in vitro to endothelial receptors such as chondroitin sulfate A and CD36. However, we observed sizeable decreases in the rigidity of infected erythrocytes in both knockout lines. Mutant parasites were further analyzed using a phospho-proteomic approach, which revealed distinct phosphorylation profiles in ghost preparations of infected erythrocytes. Knockout parasites showed a significant reduction in the level of phosphorylation of a protein of approximately 80 kDa for FIKK12-KO in trophozoite stage and a large protein of about 300 kDa for FIKK7.1-KO in schizont stage. CONCLUSIONS: Our results suggest that FIKK members phosphorylate different membrane skeleton proteins of the infected erythrocyte in a stage-specific manner, inducing alterations in the mechanical properties of the parasite-infected red blood cell. This suggests that these host cell modifications may contribute to the parasites' survival in the circulation of the human host.